KOMUNIKASI INFORMASI DAN EDUKASI PENCEGAHAN PENYAKIT MULUT DAN KUKU PADA SAPI BALI - Merdana, I Made; Sudimartini, Luh Made; Samsuri, Samsuri; Ardana, Ida Bagus Komang (Buletin Udayana Mengabdi; Vol 23 No 6 (2024): Buletin Udayana Mengabdi, 2024)
Community service has been carried out in the form of Communication, Information, and Education (KIE) for the Prevention of Foot and Mouth Disease (FMD) in Bali Cattle at the Karya Sejati Summit, Sumberkima Village, Gerogak District, Buleleng on August 19, 2023. This activity implements the Udayana Serve Program (PUM), which synergized with KKN PPM Udayana University Period XXVII 2023 performance. In implementing KKN PUM, this KIE activity becomes a work program in increasing production. The methods applied at KIE include counseling, technical guidance, and making PMK and biosecurity posters. The extension and technical guidance activities were successfully attended by 16 breeders with great enthusiasm. KIE was also carried out by distributing 50 FMD posters and 50 posters about biosecurity to surrounding livestock farmers. Counseling and technical guidance were provided by lecturers together with students and Veterinary Medicine from the Buleleng Regency Agricultural Service. Biosecurity practices are carried out by spraying the cage using disinfectant. The activity continued with controlling disease vectors, especially ticks and flies, using insecticides on 56 cattle. It can be concluded that KIE activities have succeeded in increasing cattle breeders' knowledge of FMD prevention measures and improving cattle's health status through controlling vectors and external parasites. Keywords: KIE, FMD, Bali cattle, veterinary medical services, KTT Karya Sejati